Poly(ethylene terephthalate) modification with the monomer from renewable resources - Piegat, A.; El Fray, M. (Polimery, 2022)
An emerging problem related to the development of biodegradable polymers from renewable resources was brought up in this work. Modification of petrochemical-based poly(ethylene terephthalate)(PET) with the use of bio-based monomer, namely dilinoleic acid (DLA) was presented. Series of multiblock copolymers containing oligo-PET as hard segments and DLA as soft segments was obtained in typical process of PET synthesis via polycondensation from the melt. PET/DLA copolymers containing Wh=30-90 wt.% of hard segments were characterized with respect to their mechanical, thermal and processing properties. It was demonstrated that at high concentration of DLA (Wh=30-40 wt.%) materials are susceptible to hydrolytic degradation.